Antimicrobial potential of Croton gossypiifolius (Euphorbiaceae) latex on species associated with human infections - Godoy, Gala; Instituto de Investigaciones Biomédicas “Francisco Javier Triana Alonso”, Facultad de Ciencias de la Salud, Universidad de Carabobo, Maracay, Venezuela (2020)
The empirical use of plants for medicinal purposes is an ancient practice. The Crotongenus specifically is frequently utilized by indigenous communities in South America to treat avariety of infections. In this work, the potency of the latex coming from the Croton gossypiifolius(Euphorbiaceae) tree as antimicrobial agent was studied. Also known as “Dragon’s blood”, itwas tested over microorganisms associated to infections in humans. The bacteria utilized wereKlebsiella pneumoniae, Escherichia coli, Staphylococcus aureus, Pseudomona aeruginosa and the fungiAspergillus niger. The “Dragon’s blood” was collected directly from the cortex of the trees by makingV shaped cuts. It was then added to nutritious agar and saburoud plates, where the bacteria andfungi were grown separately for the optimum time and temperature of each species. An inhibitionof the growth of S. aureus was observed. To quantify this inhibitory effect, S. aureus was cultivatedin a Luria Bertani liquid medium adding different latex concentrations (0.6%, 1.25%, 1.9%, 2.5%,3.3%) for 6 hours on each concentration. The growth was measured in Petri plates as colonyformingunits per ml (CFU/ml). A dose dependent effect was observed. For 0.6% the mean growthwas 900 CFU/ml, and the growth value decreased as the latex concentration increased until thesmallest value of 10 CFU/ml was observed when the concentration was 3.0%. The latex did notcause any inhibition in the growth of the bacteria E. coli, K. pneumoniae y P. aeruginosa, nor the fungiA. niger but it did inhibit the growth of S. aureus and the effect was dose dependent.